Assessment engine oil using UKM acoustic emission energy viscosity model (EAEUKM) - Othman, Inayatullah; Nordin, Jamaludin; Mohd Jailani, Mohd Nor; Fauziah, Mat; Aziz, Baharuddin (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.